2012
DOI: 10.5588/ijtld.11.0163
|View full text |Cite
|
Sign up to set email alerts
|

Drug lymphocyte stimulation test is not useful for side effects of anti-tuberculosis drugs despite its timing

Abstract: DLST is not useful for determining the causative drug in patients with rash, hepatitis or fever reactions to anti-tuberculosis drugs, regardless of when it is performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, the validity of DLST for testing anti-TB drugs remains controversial, and only two previously reported patients with RFP-induced pneumonitis were positive for DLST (6,8). In fact, the sensitivity of DLST for RFP has been reported to be only 13.6% (11), while another report concluded that DLST is not useful for diagnosing drug-induced pneumonitis (12).…”
Section: Discussionmentioning
confidence: 94%
“…However, the validity of DLST for testing anti-TB drugs remains controversial, and only two previously reported patients with RFP-induced pneumonitis were positive for DLST (6,8). In fact, the sensitivity of DLST for RFP has been reported to be only 13.6% (11), while another report concluded that DLST is not useful for diagnosing drug-induced pneumonitis (12).…”
Section: Discussionmentioning
confidence: 94%